Modeling viral kinetics and treatment outcome during alisporivir interferon‐free treatment in hepatitis C virus genotype 2 and 3 patients. Issue 5 (1st April 2014) - Guedj, Jeremie; Yu, Jing; Levi, Micha; Li, Bin; Kern, Steven; Naoumov, Nikolai V.; Perelson, Alan S.
<x xml:space="preserve">Abstract</x> Alisporivir (ALV) is a cyclophilin inhibitor with pan‐genotypic activity against hepatitis C virus (HCV). Here, we characterize the viral kinetics observed in 249 patients infected with HCV genotypes 2 or 3 and treated for 6 weeks with different doses of ALV with or without ribavirin (RBV). We use this model to predict the effects of treatment duration and different doses of ALV plus RBV on sustained virologic response (SVR). Continuous viral decline was observed in 214 (86%) patients that could be well described by the model. All doses led to a high level of antiviral effectiveness equal to 0.98, 0.96, and 0.90 in patients treated with 1, 000, 800, and 600 mg of ALV once‐daily, respectively. Patients that received RBV had a significantly faster rate of viral decline, which was attributed to an enhanced loss rate of infected cells, δ (mean δ = 0.35 d−1 vs. 0.21 d−1 in patients ± RBV, respectively; P = 0.0001). The remaining 35 patients (14%) had a suboptimal response with flat or increasing levels of HCV RNA after 1 week of treatment, which was associated with ALV monotherapy, high body weight, and low RBV levels in patients that received ALV plus RBV. Assuming full compliance and the same proportion of suboptimal responders, the model predicted 71% and 79% SVR after ALV 400 mg with RBV 400 mg twice‐daily for 24 and 36 weeks, respectively. The model predicted that response‐guided treatment could allow a reduction in mean treatment duration to 25.3 weeks and attain a 78.6% SVR rate. Conclusion: ALV plus RBV may represent an effective IFN‐free treatment that is predicted to achieve high SVR rates in patients with HCV genotype 2 or 3 infection. (Hepatology 2014;59:1706–1714)